Strategi Pembangunan Reformasi Birokrasi Guna Mewujudkan Organisasi Bebas Korupsi dan Pelayanan Publik Optimal - Harefa, Faonaso Refa; F. Harsono, Cecilia (Universitas Muhammadiyah Mataram, 2025)
This article aims to formulate the influence of the Integrity Zone launch strategy in the sub-work unit of the Ministry of Defense's Research and Development Agency (Balitbang) to accelerate Bureaucratic Recalibration and realize the Public Integrity Zone. To obtain comprehensive results, this article uses a mixed approach, combining qualitative and quantitative analysis. Data were collected through discussions, technical guidance, in-depth interviews with Experts, and document analysis. Qualitative data were processed using NVivo and Quantitative data using a structural system model. The study shows that the Integrity Zone launch strategy improves employee understanding and roles in managing a clean and accountable organization. In addition, bureaucratic productivity and efficiency significantly increased as a result of the involvement of leaders in providing strategic direction, the benefits of guidance from resource persons who have achieved Public Integrity Zone status, and active participation of employees who play an active role in being responsible for preparing their work units to become areas for the Integrity Zone (ZI). These findings indicate that the launch of the Integrity Zone is very important to help organizations adapt to environmental changes and technological advances. The limitation of this study lies in the scope of the analysis which is limited to the sub-work units of the Ministry of Defense's Research and Development Agency, so that generalization of the results to all ministries requires caution. This study provides original value by recommending the expansion of the implementation of the Integrity Zone to organizational units of the Indonesian National Army to accelerate the achievement of comprehensive bureaucratic reform within the Ministry of Defense. In conclusion, the launch of the Integrity Zone is a strategic step towards a clean organization, and oriented towards public service.